CORRELATION BETWEEN FOOD LITERACY AND DIET COMPLIANCE AMONG DIABETIC PATIENTS IN RIVER STATE, NIGERIA - Kio Ann Uwuma , Chima (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Diabetes is a health challenge that has accounted for many deaths and morbidities worldwide. The growing burden of diabetes and the inability to find a complete cure necessitate proper self-management. Evidence has shown that proper dietary guidelines slow the progression of the disease. However, little is known about the relationship between food literacy and dietary compliance in patients with diabetes. Two hundred and eight diabetic patients attending the public health centers in River State, Nigeria, participated in the study. They included 116 (55.8%) males and 92 (44.2%) females. The respondents completed a self-reported measure of food literacy with an oral interview. The analysis showed that food literacy statistically significantly predicted the respondent's dietary compliance at F (1,206), 138.97, P .000). Notably, the result indicated that food literacy contributed about 45.1% of the variation in dietary compliance among the respondents. Thus, food literacy was recommended to be an essential determinant of dietary compliance. The implication of the study is discussed.